2022
DOI: 10.1007/s12519-022-00515-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term physical, mental and social health effects of COVID-19 in the pediatric population: a scoping review

Abstract: Background The majority of coronavirus disease 2019 (COVID-19) symptom presentations in adults and children appear to run their course within a couple of weeks. However, a subgroup of adults has started to emerge with effects lasting several months or more after initial infection, which raises questions about the long-term physical, mental and social health effects of COVID-19 in the pediatric population. The purpose of this review was to determine these impacts well into the second year of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 73 publications
2
20
0
Order By: Relevance
“…Given the assorted symptoms associated with long COVID, which may represent multisystemic effects, partnerships between medical and mental health disciplines (e.g., neurology, rehabilitation medicine, neuropsychology), and across settings (e.g., medical, mental health, and school teams) will likely be integral in supporting patients’ symptom management, well-being, and return to day-to-day functioning. Cognitive difficulties such as concentration difficulties are very commonly reported long after COVID illness as shown in our clinical sample and in prior case studies with children ( Berg et al., 2022 ; Borch et al., 2022 ; Borel et al., 2022 ; Brackel et al., 2021 ; Ludvigsson, 2021 ). Because of their training in both the medical/neurological and psychological fields, neuropsychologists are uniquely poised to understand the many factors that might be contributing to these cognitive difficulties; communicate the identified brain–behavior relationships to patients, families, school personnel, and other providers; and tailor treatment and educational plans as appropriate.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Given the assorted symptoms associated with long COVID, which may represent multisystemic effects, partnerships between medical and mental health disciplines (e.g., neurology, rehabilitation medicine, neuropsychology), and across settings (e.g., medical, mental health, and school teams) will likely be integral in supporting patients’ symptom management, well-being, and return to day-to-day functioning. Cognitive difficulties such as concentration difficulties are very commonly reported long after COVID illness as shown in our clinical sample and in prior case studies with children ( Berg et al., 2022 ; Borch et al., 2022 ; Borel et al., 2022 ; Brackel et al., 2021 ; Ludvigsson, 2021 ). Because of their training in both the medical/neurological and psychological fields, neuropsychologists are uniquely poised to understand the many factors that might be contributing to these cognitive difficulties; communicate the identified brain–behavior relationships to patients, families, school personnel, and other providers; and tailor treatment and educational plans as appropriate.…”
Section: Discussionsupporting
confidence: 77%
“…It was suggested that adults with prolonged symptoms may experience a constellation of physical and cognitive symptoms similar to myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) or mild traumatic brain injury (mTBI). At present, the neurological and cognitive sequelae of children remain largely unknown, although recent case reports suggest affected youth and their parents similarly endorse complaints of fatigue, labored breathing, and attention/concentration difficulties ( Brackel et al., 2021 ; Ludvigsson, 2021 ) in addition to sleep disturbances and memory difficulties ( Borel et al., 2022 ). To our knowledge, most of these studies rely on self or parent report and there are no existing investigations on the cognitive sequelae of long COVID in youth based on objective cognitive test measures.…”
Section: Introductionmentioning
confidence: 99%
“…This approach, however, relies on multiple low-quality systematic reviews, which usually fail on the definition of their methods (protocol), the rigour of their search, and the ambiguity in their inclusion criteria. Nevertheless, existing reviews highlighted similar findings to our evidence map, including the lack of controlled studies, the need for prospective studies with long-term follow-up and focus on overall recovery and health-related quality of life, and a paucity of research in children and in vaccinated people [ 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 76%
“…At-risk individuals may experience new onset of mental health problems, while those with pre-existing mental health problems may experience symptomatic exacerbation—especially if access to mental health services is impeded due to COVID-19 regulations [ 21 , 22 ]. To date, empirical studies of the mental wellbeing burden of the pandemic are scarce in this vulnerable population—particularly longitudinal studies [ 23 ]. A better understanding is of clinical relevance, since this enables health professionals to incorporate pandemic-related effects into their care for their patients.…”
Section: Introductionmentioning
confidence: 99%